PROSECUTOR'S OFFICE AND PROSECUTOR'S INSPECTION IN UZBEKISTAN CHARACTERISTICS OF INCREASE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article deals with the prosecutor's office in the judicial systemdirections and activities of the prosecutor based on the coordination of activitie issues such as the invaluable service and role of their duties in our state.